Web Ranking and Rating Server Usng Web Service - Abdul Latef, F. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The amount of information on the web is growing rapidly and number of web sites becomes huge, so set of web applications used to help user and give him some information about these sites, especially in e- business, news and sites introduce services.Since Web site is built by comparatively free description, it is difficult to perform absolute evaluation. So, rating of Web site is performed from various viewpoints.In this paper we proposed method for ranking and rating using the web service and java script to motivation remote server and return some public information to the site user and other private information to owner.